Students’ Perceptions of the Use of a Snake and Ladder Board Game in Learning Vocabulary at the English Club of SMK N 1 Banyumas - Maria Dimitrij Angie Pavita (English Language and Education Spectrum, 2022)
This research examines the use of a snake and ladder board game implemented in SMK N 1 Banyumas. This research aimed to explore students’ perceptions of the use of a snake and ladder board game to facilitate vocabulary learning for the students participating in the English Club of SMK N 1 Banyumas. The researcher formulated two different issues in this study: (1) The students’ perceptions of the implementation of a snake and ladder board game for English Club students’ SMK N 1 Banyumas and (2) How the use of snake and ladder board game could enhance the English Club students’ vocabulary mastery at SMA SMK N 1 Banyumas. A case study as the research design was applied in this research. The research participants were thirty-three (33) students and an English teacher of the English Club at SMK N 1 Banyumas. In collecting data, the researcher conducted observation, distributed questionnaires, and conducted interviews with students and an English teacher of the English Club. The data were presented in the form of narrative descriptions. This study indicates that the participants were interested in using a snake and ladder board game. In fact, the participants realised that the use of a snake and ladder game could encourage students’ ability to enrich their vocabulary and suggested that the game is used for learning vocabulary in class.